Elevated sL1‐CAM levels in BALF and serum of IPF patients. Issue 1 (27th November 2015) - Zhang, Yingwei; Bi, Lintao; Qiu, Yuying; Wang, Yang; Ding, Jingjing; Zhuang, Yi; Tian, Yaqiong; Cai, Hourong
Abstract: Background and objective: IPF is a form of interstitial pneumonia of unknown origin that has a poor prognosis for which current treatments are limited. Recent studies have shown that EMT plays a role in IPF and tumour metastasis. L1‐CAM has also been linked to EMT during tumour development and tumour metastasis. Our aim was to determine prospectively the level of L1‐CAM in IPF patients. Methods: Forty consecutive Chinese patients (with IPF, 16; LC, 12; and CC, 12), but no apparent lung or other organ's diseases were enrolled. Soluble L1‐CAM (sL1‐CAM), TGF‐β1, PDGF, γ‐INF levels in BALF and serum sL1‐CAM were measured using ELISA. Results: BALF sL1‐CAM levels of IPF, LC and CC patients were 10.87 ± 0.88 ng/mL, 6.34 ± 0.67 ng/mL and 5.43 ± 0.65 ng/mL, respectively. BALF sL1‐CAM concentration of IPF patients was significantly higher than that in LC and in CC patients. Besides, serum sL1‐CAM levels in patients with IPF, LC and CC were 9.60 ± 1.41 ng/mL, 9.82 ± 0.72 ng/mL and 5.41 ± 1.07 ng/mL, respectively. The serum sL1‐CAM levels in patients with IPF and LC were significantly higher than those in patients with CC ( P < 0.001, respectively). Conclusions: The concentrations of sL1‐CAM both in BALF and in serum of patients with IPF are markedly increased compared with controls. This indicates that L1‐CAM might be involved in the pathogenesis of IPF as well as that of LC. Abstract : The aim of this study was to analyse prospectively the level of sL1‐CAM in IPF patients. The concentrations of sL1‐CAM in IPF patients are markedly increased compared with controls. This indicates that L1‐CAM might be involved in the pathogenesis of IPF as well as in LC.